Enlightenment Orientalism in the American mind, 1770-1807 - Pangborn, Matthew H. (New York, NY : Routledge, 2019)
"This study engages with the emerging field of energy humanities to provide close readings of several early American oriental-observer tales. The popular genre of orientalism offered Americans a means to critique new ideas of identity, history, and nationality accompanying protoindustrialization and a growing consumerism. The tales thus express a complex self-reflection during a time when America's exploitation of its energy resources and its engagement in a Franco-British world-system was transforming the daily life of its citizens. The genre of the oriental observer, this study argues, offers intriguing glimpses of a nation becoming strange in the eyes of its own inhabitants"--
Introduction: America's "Oriental Mirror" -- American Oriental Tales -- Mobility, Luxury, Textuality, and Liberty in Father Bombo's Pilgrimage to Mecca -- The "Oriental" Threat to the Body of America in the Algerine Spy in Pennsylvania -- The Oriental Spectacle of Western Power in the Algerine Captive -- History, Nature, and National Progress in Letters of Shahcoolen (1801-1802) -- Woman, Orientalism, and Empire in Salmagundi (1807-1808) -- Epilogue: the Haunted House of Oriental History in the Alhambra
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
eBooks on EBSCOhost
Keywords: Orientalism -- United States -- History -- 18th century; Orientalism -- United States -- History -- 19th century; Energy consumption -- United States -- History; Middle East -- Foreign public opinion, American; Asia -- Foreign public opinion, American; Orientalisme -- États-Unis -- Histoire -- 18e siècle.; Orientalisme -- États-Unis -- Histoire -- 19e siècle.; Énergie -- Consommation -- États-Unis -- Histoire; SOCIAL SCIENCE -- General; Energy consumption; Orientalism; Public opinion, American; Asia; Middle East; United States; 1700-1899; History